Scientific Advice on the estimation of surplus for Sustainable Fisheries Partnership Agreements. - García-Isarch, Eva; Gascuel, Didier; Guijarro-García, Elena; Gaertner, Daniel; Merino, Gorka; Coelho, Rui; Rosa, Daniela; Murua, Hilario; Wakeford, Robert; Jouffre, Didier; Figueiredo, Ivone; Abaunza, Pablo; et al. (2016)
Scientific advice on the concept of surplus, as defined by the UNCLOS, was provided for three types of Sustainable Fisheries Partnership Agreements (SFPAs): i) Mixed SFPAs in West Africa, ii) Tuna SFPAs and iii) SFPA with Greenland. For Mixed SFPAs in West Africa, methods for surplus computation were defined, including alternatives for cases of data limited stocks. These methods may use as input five parameters that could be obtained from those recent stocks assessments that are representative of the current stock status. Surplus estimates would need to be regularly updated (ideally, yearly), according to every new stock assessments and following the enforcement of a management plan (or, by default, according to a transition scheme towards reaching Fmsy in 2020). In the case of West African transboundary stocks, a theoretical share of the surplus could be calculated using a standard rule based on historical catches within EEZs. The Surplus concept is not applicable for Tuna SFPAs, due to the high migratory character of tuna or tuna-like species, the fact that these stocks are mostly found in areas beyond national jurisdictions, the lack of direct estimates of local abundance and impossibility to calculate the capacity of the coastal States. For the SFPA with Greenland, Surplus is considered as any TAC allocated to Greenland and not utilised by this coastal State.